AB0794 Development of a computerized animated activity questionnaire (aaq) to measure activity limitations in patients with hip and knee osteoarthritis. (23rd January 2014) - Peter, W. F.; de Vet, H. C.; Boers, M.; Harlaar, J.; Roorda, L. D.; Poolman, R. W.; Scholtes, V. A.; Steultjens, M.; Roos, E. M.; Guillemin, F.; Rat, C.; Benedetti, M. G.; et al.
Abstract : Background: Self-report questionnaires and performance-based tests correlate moderately in measuring activity limitations, indicating that they are measuring different aspects. Self-reports measures mainly the patients' perception which may lead to cross-cultural differences. Performance-based tests measure an artificial situation and might be a burden for patients, requires physical presence and is time- and money consuming. An alternative method is a computerized animated activity questionnaire (AAQ). Besides being a solution for the abovementioned disadvantages the AAQ do not need reading ability and translation for international use. Objectives: To develop a computerized AAQ, a new method to assess activity limitations in patients with hip and knee osteoarthritis (OA). Methods: First the construct to be measured is described. For content validity the ICF core set for hip and knee OA and self-report questionnaires were consulted. In addition two patient focus group sessions were performed to identify the most limited activities, included the different executions of those activities. Subsequently a specialized company videotaped the executions of the activities (performed by physical therapists as actors) using motion capture and transformed the videos into animations. A virtual environment was created in the animation in order to imitate a standard real life situation as much as possible. A computerized questionnaire was composed. Results: Seventeen basic daily activities were selected. For each activity 3 to 5 levels of executions were filmed. Subsequently video animations were produced of all the levels of execution of the 17 activities. In the final AAQ patients are asked to choose the video that best matches their own performance. Conclusions: A new Patient Reported Outcome method to measure activity limitations in patients with hip and knee OA was developed: the computerized AAQ. The AAQ shows animations of basic daily activities in virtual, real life situations. The AAQ can minimize the patients' perception, is less burdensome and save time/money. Furthermore no reading ability and translation is needed. On-going research focuses on assessing (cross-cultural) validity and reliability. Funding This project is funded by the EULAR Grant for research on Patient Reported Outcome. Disclosure of Interest: None Declared